Outcome of sleepiness and fatigue scores in obstructive sleep apnea syndrome patients with and without restless legs syndrome after nasal CPAP - Rodrigues,Raimundo Nonato Delgado (2007)
BACKGROUND & PURPOSE: The association of obstructive sleep apnea syndrome (OSAS) and restless legs syndrome (RLS) has been reported in the literature for many years. Both conditions may be responsible for fatigue and somnolence complaints secondary to nocturnal sleep disruption. The primary concern of this study is to evaluate the outcome of fatigue and daytime sleepiness symptoms at baseline and after continuous positive air pressure (CPAP) treatment in OSAS patients with and without RLS. METHOD: A prospective and comparative study between a group of 13 patients with OSAS and a group of 17 patients with OSAS+RLS. Laboratory blood tests and polysomnography were performed at baseline. The Epworth Sleepiness Scale (ESS) and the Pichots questionnaire of fatigue/depression (PIC) were applied before and after 3 months of CPAP treatment. Results were compared. RESULTS: No significant differences were found on PSG and laboratory results at baseline. Both groups had similar ESS and PIC scores at baseline (p=0.73 and 0.08, respectively). After n-CPAP, OSAS+RLS patients showed higher ESS and PIC scores (p=0.017 and 0.03, respectively). CONCLUSIONS: Despite a favorable general response, n-CPAP seemed less effective in treating fatigue and sleepiness in the OSAS+RLS group.